Experimental Examination on Nitrous Oxide Accumulation during Nitrification in a Freshwater Lake - YOH, Muneoki (Japanese Journal of Limnology (Rikusuigaku Zasshi), 1990)
The N2O production during nitrification was studied in Lake Kizaki by vertical observations and two incubation experiments. The apparent N2O production (ΔN2O), the difference between observed and atmospheric-equilibrium concentration, was highly correlated with apparent oxygen consumption (-ΔO2), in situ NO3- concentration and the amount of NH4+ decrease with time, indicating that N2O was produced by the nitrification process. In a long-term in situ incubation, simultaneous accumulations of NO3- and N2O were observed, the amounts of which were comparable to the in situ changes, suggesting their in situ productions. Both NO3- and N2O productions were greatly enhanced by an NH4+ enrichment after the emergence of nitrification activity. From both vertical observations and long-term in situ incubations, the yield of N2O relative to NO3- production was estimated to be about 0.1% during the active nitrification period. But thereafter, the obtained yields were appreciably higher. Another incubation experiment also showed that N2O production was delayed several days compared to NO3- production, indicating that N2O production was accelerated in the late phase of nitrification. The physiological state of nitrifiers was suggested to be of some importance for such phenomena. Nitrapyrin, a specific inhibitor of nitrification, was found not to be very effective for N2O formations in contrast with NO3- productions completely inhibited, suggesting a possibility of some N2O sources other than autotrophic nitrification.